Case Report: Reversible alien hand syndrome caused by cerebral infarction - Lin, Guo-Liang; Yu, Xiao-Qian; Cai, Han-Yu; Zhou, Ru-Yi; Li, Xiao-Tian; Zhang, Xiong; Wang, Jian-Yong (Frontiers in Human Neuroscience, 2025)
IntroductionAlien hand syndrome (AHS) is a rare apraxia syndrome that may arise from several neurological disorders including stroke. Given the uncommon symptoms, stroke with AHS as its main manifestation often results in diagnostic challenges and treatment delays.Case presentationWe herein presented a case of post-stroke AHS caused by corpus callosum infarction. We prescribed him aspirin, clopidogrel, atorvastatin and memantine, and his AHS was remitted completely within 8 days.ConclusionAHS is a rare manifestation of cerebral infarction that is generally reversible. Rapid identification of post-stroke AHS and early initiation of treatment are important to improve patient’s prognosis.